Indirect Effect of Self-Regulated Exercise on Mood Through Self-Efficacy Changes - James J. Annesi (New Prairie Press, 2023)
To improve deficient long-term effects, an improved understanding of psychosocial factors occurring within behavioral obesity treatments is required. The aim of this study was to suggest paths from changes in self-regulation toward reduced negative mood to inform the direction of more comprehensive investigations and treatment foci. Initially low active women (N = 87) participated in a theory-driven community-based behavioral obesity program emphasizing self-regulation and exercise. There were significant (ps < .001) improvements in exercise amounts, exercise-related self-regulation and self- efficacy, negative mood, and emotional eating during the weight loss phase of baseline-Month 6, and significant (ps < .01) deteriorations during the weight-loss maintenance phase of Month 6-Month 24. During both phases, significant paths (95% CIs [-0.31, -0.01], [-0.14, -0.01], and [-0.50, -0.01]) from changes in self-regulation toward reduced negative mood were through self-efficacy, but not exercise change itself. The mood change-emotional eating change relationships were significant (95% CIs [0.16, 0.39] and [0.19, 0.48]). Although extensions of this research are required to better understand long-term obesity intervention processes, the present findings suggest importance of treatment foci on identified psychological mechanisms of exercise treatment-mood change relationships.